Overview of Adverse Outcome Pathways and Current Applications on Nanomaterials - Rolo, Dora (2022)
Nanomaterials (NMs) have important and useful applications in chemical industry, electronics, pharmaceuticals, food and others. Their rapid proliferation presents a dilemma to regulators regarding hazard identification and increased concerns for public health. The Adverse Outcome Pathways (AOPs) are innovative central elements of a toxicological knowledge framework, developed for supporting chemical risk assessment based on mechanistic reasoning. AOPs describe a sequence of causally linked events at different levels of biological organisation, triggered by exposure to a stressor (like chemicals or NMs) leading to an adverse health effect in humans or wildlife. The integrative analysis of the cellular and molecular mechanisms of nanotoxicity towards the identification of connected adverse outcomes drives a sequential line – an AOP landscape definition. Each defined AOP is available for crossing data, linking known and unknown landscapes, reducing the reliance on animal studies, associated costs and ethical issues. NMs have unique properties, with specific associated toxicological challenges, which may represent unknown AOP landscapes. In this chapter, an overview of AOPs as important novel strategic tools in nanotoxicology is presented, highlighting the current applications in hazard identification and human health risk assessment.